A new global regulator that facilitates the co‐metabolization of polyaromatic hydrocarbons and other nutrients in Novosphingobium. (22nd April 2021) - Rojo, Fernando
Summary: In an article in this issue of Environmental Microbiology, Segura et al . report the identification of an unusual global regulator in Novosphingobium sp. HR1a, a metabolically versatile bacterial strain isolated from the rhizosphere able to assimilate a wide range of polyaromatic hydrocarbons (PAHs). Physiological and transcriptomic assays suggest that this regulator, named PahT, activates the expression of genes involved in the assimilation of PAHs, and of compounds such as sugars and acetate, facilitating their co‐metabolism. This effect is the opposite to the carbon catabolite repression strategy that allows metabolically versatile bacteria to favour the use of some compounds over others. PahT was found to stimulate sugar uptake and metabolization in the presence and absence of PAHs and to facilitate microaerobic respiration if PAHs were present. A survey of the genomes of several Sphingomonadaceae members showed that PahT is not present in all strains of this family, but that it is strongly associated with PAH degradation genes. Since not all PAH‐degrading strains contain pahT, it seems that PahT is not essential for PAH degradation but likely provides a selective advantage to PAH‐degrading strains in environments such as the rhizosphere where other potential carbon sources are available.